A US metropolitan county health department's response to a measles outbreak in a childcare facility – challenges faced and lessons learned. (January 2022) - Meyer, Diane; Trotochaud, Marc; Ferguson, Lisa; Vines, Jennifer; Barlow, Russell; Nuzzo, Jennifer B
Aims: In June 2018, the Multnomah County Health Department located in Portland, Oregon, US, responded to a measles exposure in a local childcare facility. This analysis describes lessons learned and challenges encountered during this measles response that may inform public health policy and help other local public health authorities prepare for measles outbreaks. These lessons will become increasingly important as measles cases continue to increase in both the US and abroad. Methods: A semi-structured videoconference interview was conducted with nine health department staff who were directly involved in the health department's response to the measles outbreak. Interview notes were iteratively discussed between all authors to identify those outbreak response challenges and lessons learned that were generalizable to the broader public health community. Results: Some of the key challenges and lessons learned included the need for increased provider recognition and reporting of measles cases, difficulty in determining which staff and children to exclude from attending daycare during the 21-day postexposure monitoring period, determining who would be prioritized to receive immunoglobulin, and the need for childcare staff vaccine status requirements. Conclusion: Lessons from this response highlight important considerations for public health practitioners and policy makers. Given the relative severity of measles and the potential for spread in facilities that serve infants and young children, the public health community must continue to address key gaps through planning and policy.